Comprehensive evaluation of two HLA‐B17 monoclonal antibodies for flow cytometry‐based HLA‐B57/B58 screening prior to abacavir prescription. (26th December 2012) - Stevens, R.; Coates, E.; Street, J.; Cook, E.; Darke, C.
Summary Hypersensitivity reactions to the drug abacavir, used to treat HIV/AIDS patients, is associated with possession of HLA‐B*57:01. We have carefully assessed two commercially available HLA‐B57/B58 murine monoclonal antibodies [0196HA and BIH0243 (One Lambda Inc.)] in a simple flow cytometry‐based assay. The evaluation involved tests on 228 reference and random samples covering 91% of all WHO recognized HLA‐A, B and C specificities. These involved donors with six different HLA‐B*57 alleles and included 19 examples of B*57:01. Both antibodies unambiguously detected B57, but there were small difference in their reactivity against B57‐positive non‐B*57:01 samples. Importantly, there was no reactivity against B57/B58‐negative samples. The possible amino acid motifs involved in the reactivity of these antibodies with B57/B58 were delineated. Thus, HLA‐B57/B58, normally present in <10% of patients, can be easily recognized using these two antibodies and further tested by a DNA‐based typing method to identify B*57:01.